Pengaruh Keahlian, Kepercayaan, Daya Tarik, Keakraban, Kesukaan, dan Kesamaan Influencer Tiktok terhadap Keterikatan Merek - Kasnowo; Ramadan Gibrihi; Anindita Imam Basri (Akmenika: Jurnal Akuntansi dan Manajemen, 2022)
This study has the effect of expertise, trust, attar ctiveness, familiarity, liking, and similarity of TikTok influencers on brand engagement. The research was conducted in the Special Region of Yogyakarta in 2022. The population of this study were all TikTok users in Yogyakarta. The sample of this research is 140 respondents. The sampling technique in this study used a non-probability sampling technique using a purposive sampling method and this study used multiple linear regression analysis. The results of this study obtained the following regression equation. The results of this study prove that expertise has a positive and significant effect on brand attachment, trust has a positive and significant effect on brand attachment, attractiveness has a positive and significant effect on brand attachment, familiarity has a positive and significant effect on brand attachment, liking has a positive and insignificant effect on engagement. brand, and similarity has a positive and significant effect on brand attachment. The results of the study of six independent variables have a simultaneous influence on buying interest. This study is explained by the adjusted R Square of 43.3%.